Surveillance Epidemiology and End Results Analysis Demonstrates Improvement in Overall Survival for Cervical Cancer Patients Treated in the Era of Concurrent Chemoradiotherapy - Hsu, Howard C.; Li, Xiaochun; Curtin, John P.; Goldberg, Judith D.; Schiff, Peter B. (Frontiers in oncology, 2015)
In February 1999, the National Cancer Institute (NCI) issued a clinical alert based on five randomized trials that reported better overall survival (OS) with concurrent chemoradiotherapy (CCRT) than with surgery or radiation alone for locoregional cervical cancer. This study analyzes data from the surveillance epidemiology and end results (SEER) program to evaluate the improvement in survival in the era of CCRT. The SEER database was queried for FIGO stages IB2-IVA cervical cancer patients treated with radiotherapy between 1995 and 2002. Patients diagnosed between 1999 and 2002 (CCRT era) were assumed to have received CCRT more frequently than patients diagnosed between 1995 and 1998 (RT era). Cases were stratified by period of diagnosis, age, and SEER region. OS and cause specific survival (CSS) were compared between the two time periods with chi-square log-rank tests. Multivariable Cox models were also used to compare OS and CSS between the two time periods, with adjustment for stratification variables and other covariates. The study included 3517 patients. Unadjusted OS and CSS were significantly improved in 1999-2002 compared with 1995-1998 (OS: p < 0.001, hazard ratio (HR): 0.81; CSS: p < 0.001, HR: 0.79). Significant improvements in OS and CSS were retained after adjustment for multiple variables (multivariable OS HR 0.78; CSS HR 0.76). Cervical cancer patients treated with radiotherapy after 1999 had improved OS and CSS compared with patients treated before 1999, likely reflecting increased usage of CCRT. This study adds to the population-level evidence supporting the adoption of CCRT as the standard of care for locoregional cervical cancer.